Psychosocial predictors of non-adherence to antihypertensive medication among Korean adults: A nationwide cross-sectional study - Kunhee Han; Hwa Sun Kim; Young Lee; Chung-woo Lee (PLoS ONE, 2026)
The objective of this study was to examine whether depressive symptoms and social vulnerability factors—including living alone, Basic Livelihood Security Program recipient status, and lack of private health insurance—are associated with non-adherence to antihypertensive medication among Korean adults. This cross-sectional analysis used nationally representative data from the Korea National Health and Nutrition Examination Survey (KNHANES), specifically the 2014 (6th cycle–2nd year), 2016 (7th–1st year), 2018 (7th–3rd year), and 2020 (8th–2nd year) cycles, the only survey years that included both depressive symptoms data and antihypertensive medication use information. Non-adherence was defined as taking prescribed medication on fewer than 20 days during the previous month. Depressive symptoms were assessed using the Patient Health Questionnaire-9. Complex survey logistic regression models were used to evaluate associations between psychosocial factors and non-adherence. Two analytic models were applied: individual models for each psychosocial variable and a combined model adjusting for age, sex, obesity, smoking, alcohol use, physical activity, diabetes, and dyslipidemia. Subgroup analyses were performed by age (<70 and ≥70 years). Among adults aged 40 years or older taking antihypertensive medication, approximately one in ten reported non-adherence. In the fully adjusted model, none of the psychosocial factors—including depressive symptoms, living alone, Basic Livelihood Security Program recipient status, or lack of private insurance—were significantly associated with non-adherence in the overall population. However, depressive symptoms were significantly associated with non-adherence among adults aged 70 years or older, whereas no significant associations were observed in younger adults or sex-specific subgroups. These findings suggest that depressive symptoms do not uniformly influence antihypertensive medication adherence across the adult population but may play a more important role in older adults. Incorporating routine screening for depressive symptoms into hypertension management for older individuals may support more effective adherence and improved clinical outcomes.